Foreign Language Anxiety in Taiwanese Student Interpreters - Chiang, Yung-Nan (Meta, 2009)
AbstractAlthough anxiety has been found to be a key variable in both interpretation performance and second language (L2) acquisition, there has been virtually no dialogue between these two fields. In order to bridge this gap, this study investigated Taiwanese undergraduate student interpreters’ foreign language (FL) anxiety using Horwitz, Horwitz et al.’s (1986) Foreign Language Classroom Anxiety Scale. Results showed that (1) Taiwanese student interpreters did have FL anxiety despite the language facility expected from them; (2) the scope of their FL anxiety was slightly less prevalent than regular Asian L2 learners, as widespread as American L2 learners, and more far-reaching than European L2 learners; and (3) the level of their FL anxiety was slightly less severe than in most of the university students from several cultural groups with various L2s, except for American college students of Arabic and Russian. Implications for pedagogy and future research are suggested.